Long-term menopause exacerbates vaginal wall support injury in ovariectomized rats by regulating amino acid synthesis and glycerophospholipid metabolism - Yu, Xia; He, Li; Lin, Wenyi; Zheng, Xuemei; Zhang, Ling; Yu, Bo; Wang, Yanjun; Yang, Zhenglin; Lin, Yonghong (Frontiers in Endocrinology, 2023)
Purpose: Menopause is a risk factor for pelvic organ prolapse (POP) and is frequently associated with diminished vaginal wall support. To uncover relevant molecular mechanisms and provide potential therapeutic targets, we evaluated changes in the vaginal wall transcriptome and metabolome in ovariectomized rats to identify important molecular changes. Methods: Sixteen adult female Sprague‒Dawley rats were randomly assigned to either the control or menopause group. Hematoxylin and eosin (H&E) staining and Masson trichrome staining were used to observe changes in the rat vaginal wall structure. Differentially expressed genes (DEGs) and metabolites (DEMs) in the vaginal wall were detected seven months following the operation by RNA-sequencing and LC‒MS, respectively. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses of DEGs and DEMs were performed. Results: We verified that long-term menopause causes vaginal wall injury by H&E and Masson trichrome staining. From the multiomics analyses, 20,669 genes and 2193 metabolites were identified. Compared with the control group, 3255 DEGs were found in the vaginal wall of long-term menopausal rats. Bioinformatics analysis showed that the DEGs were mainly enriched in mechanistic pathways, including cell‒cell junction, extracellular matrix, muscle tissue developments, the PI3K-Akt signaling pathway, the MAPK signaling pathway, tight junctions and the Wnt signaling pathway. Additionally, 313 DEMs were found, and they consisted mostly of amino acids and their metabolites. DEMs were also enriched in mechanistic pathways, such as glycine, serine and threonine metabolism, glycerophospholipid metabolism, gap junctions and ferroptosis. Coexpression analysis of DEGs and DEMs revealed that biosynthesis of amino acids (isocitric acid and PKM) and glycerophospholipid metabolism (1-(9Z-hexadecenoyl)-sn-glycero-3-phosphocholine and PGS1) are critical metabolic pathways, suggesting that POP induced by menopause may be associated with the regulation of these processes. Conclusion: The findings showed that long-term menopause greatly exacerbated vaginal wall support injury by decreasing the biosynthesis of amino acids and interfering with glycerophospholipid metabolism, which may result in POP. This study not only clarified that long-term menopause exacerbates vaginal wall damage but also provided insight into the potential molecular mechanisms by which long-term menopause induces POP.